Platinum clusters with precise numbers of atoms for preparative-scale catalysis - Takane Imaoka (Nature Portfolio, 2017)
The catalytic activity of a noble metal nanocluster is tied to its atomicity. Here, the authors report an atom-precise, fully scalable synthesis of platinum clusters from molecular ring precursors, and show that a variation of only one atom can dramatically change a cluster’s reactivity.